Protease Enzyme Producing Microorganisms and Their Application in Disinfection of Infected Wounds - Putri, Yumna Syaza Kani (Dinasti Health and Pharmacy Science, 2024)
Wound infection is a serious clinical challenge, mainly due to increasing antibiotic resistance and biofilm formation by pathogenic microorganisms. Protease enzymes produced by various microorganisms, especially bacteria, have shown potential in decomposing necrotic tissues, destroying biofilms, and enhancing the efficacy of other antimicrobial agents. The literature shows that microorganisms such as Bacillus subtilis, Pseudomonas aeruginosa, and Streptomyces spp. produce proteases with significant pharmacological activities. The application of these enzymes in topical formulations, bioactive wound dressings, and combination therapies has become the focus of research in the fields of pharmaceuticals and medical biotechnology. This article aims to review the characteristics of protease-producing microorganisms, the mechanism of action of enzymes in the wound disinfection process, and the challenges and prospects of their future applications. This review is expected to be a scientific basis for the development of biotechnology-based wound therapy.